Array comparative genomic hybridisation of 52 subjects with a Smith–Magenis-like phenotype: identification of dosage sensitive loci also associated with schizophrenia, autism, and developmental delay - Williams, Stephen R; Girirajan, Santhosh; Tegay, David; Nowak, Norma; Hatchwell, Eli; Elsea, Sarah H (Journal of medical genetics, 2010)
BackgroundSmith-Magenis syndrome (SMS) is caused by del(17)(p11.2), including the retinoic acid induced 1 gene (RAI1), or mutation of RAI1. Haploinsufficiency of RAI1 results in developmental delay, mental retardation, sleep disturbance, self-abusive behaviors, and most features commonly seen in SMS. In this study, 52 subjects were referred for molecular analysis of RAI1 due to the presence of an SMS-like phenotype in each case. For this cohort, deletion and mutation analyses of RAI1 were negative; thus, the clinical diagnosis of SMS could not be confirmed and suggested that at least one other locus was responsible for the phenotype(s) observed.MethodsHere, we present whole-genome array comparative genomic hybridization and detailed phenotypic data of these 52 subjects.ResultsThis SMS-like cohort exhibited developmental delays, sleep disturbance, self-abusive behaviors, motor dysfunction, and hyperactivity of the same type and prevalence as that of SMS. In this analysis, we identified at least 5 new loci that likely contribute to the SMS-like phenotype, including CNVs that were found in more than one subject. Genes in these regions function in development, neurological integrity, and morphology, all of which are affected in SMS.ConclusionsGiven the phenotypic overlap between SMS and the SMS-like cases, these data may provide some insight into the function of RAI1, including the pathways in which it may be involved and the genes it may regulate. These data will improve diagnosis, understanding, and potentially treatment of these complex behavior and mental retardation syndromes.